2014
DOI: 10.5946/ce.2014.47.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Pancreatic Calculi

Abstract: Chronic pancreatitis is a progressive inflammatory disease that destroys pancreatic parenchyma and alters ductal stricture, leading to ductal destruction and abdominal pain. Pancreatic duct stones (PDSs) are a common complication of chronic pancreatitis that requires treatment to relieve abdominal pain and improve pancreas function. Endoscopic therapy, extracorporeal shock wave lithotripsy (ESWL), and surgery are treatment modalities of PDSs, although lingering controversies have hindered a consensus recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…On the other hand, endoscopic treatment is considered a less invasive and effective modality despite its limitations for use in all patients. Nevertheless, the combination of endoscopic therapy and ESWL can be regarded as first-line treatment in high-risk patients for surgery or such with relevant indications[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, endoscopic treatment is considered a less invasive and effective modality despite its limitations for use in all patients. Nevertheless, the combination of endoscopic therapy and ESWL can be regarded as first-line treatment in high-risk patients for surgery or such with relevant indications[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is a strong association with chronic pancreatitis (CP), which is present in 50–90% of these patients [ 4 ]. However, CP in the long term can be associated with a variety of complications affecting both the pancreas (pancreatic pseudocyst, pancreatitis and pancreatic adenocarcinoma) and the adjacent anatomical structures, causing biliary and duodenal obstruction [ 3 , 5 , 6 ]. Moreover, PC is found in less than 1% of a random sample of the population, mainly in older people, but also in younger people and rarely in children [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pancreatitis encompasses a wide range of progressive fibro-inflammatory processes of the exocrine pancreas that eventually lead to damage of the gland, leading to abdominal pain, endocrine (diabetes) and exocrine insufficiency (steatorrhea). Pancreatic duct stones, a common complication of chronic pancreatitis, develop during the natural course of disease and are observed in 90% patients [ 1 ]. Current treatment options include endoscopic therapy, extracorporeal shock wave lithotripsy (ESWL) and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous published studies, major complications were classified into five groups: post-ESWL pancreatitis, bleeding, infection, steinstrasse and perforation [ 6 , 9 ]. It is reported that the rate of post-ESWL pancreatitis ranges from 6.3 to 12.5% [ 1 ]. According to previous data in our center, post-ESWL pancreatitis was the most common complication, with an overall occurrence rate of 6.8% for the first P-ESWL sessions.…”
Section: Introductionmentioning
confidence: 99%